1987
DOI: 10.1159/000124806
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Release of Dopamine, Luteinizing Hormone-Releasing Hormone and Thyrotropin-Releasing Hormone in Male Rats Bearing a Prolactin-Secreting Tumor

Abstract: The present study was concerned with the effects of a transplantable prolactin-secreting pituitary tumor (7315b) on the hypothalamic release of dopamine, luteinizing hormone-releasing hormone (LHRH) and thyrotropin-releasing hormone (TRH) in gonadectomized, adrenalectomized male rats bearing subcutaneously a testosterone capsule and a corticosterone pellet. Similar male rats not inoculated with tumor served as controls. The rats were studied 3–4 weeks after tumor inoculation, while they were anesthetized with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 26 publications
(46 reference statements)
1
37
0
Order By: Relevance
“…Unlike in the rat (Voogt et al 1987, Koike et al 1991, PRL treatment does not appear to suppress hypothalamic GNRH secretion in sheep. Infusion of PRL into the third ventricle of the brain has little or no effect on episodic LH release in either rams (Lincoln & Tortonese 1997, Romanowicz et al 2004 or ewes (Curlewis & McNeilly 1991, Misztal et al 2005.…”
Section: Introductionmentioning
confidence: 56%
“…Unlike in the rat (Voogt et al 1987, Koike et al 1991, PRL treatment does not appear to suppress hypothalamic GNRH secretion in sheep. Infusion of PRL into the third ventricle of the brain has little or no effect on episodic LH release in either rams (Lincoln & Tortonese 1997, Romanowicz et al 2004 or ewes (Curlewis & McNeilly 1991, Misztal et al 2005.…”
Section: Introductionmentioning
confidence: 56%
“…Therefore, as long as the plasma concentrations of progesterone remain elevated, follicular growth will be retarded and small LH surges will occur. It also has been reported that hyperprolactinemia can reduce the secretions of LH [8,14] and GnRH [3,14,38]. Recent reports have suggested that CRH is probably involved in the suppressed secretion of LH during hyperprolactinemia [7,15].…”
Section: Discussionmentioning
confidence: 96%
“…This negative result does not rule out the participation of the adrenergic innervation o f the M E in the regulation of the CRH-41 release into the portal system, especially as a 10-fold increase in the adrenaline concentration in the perfusate (10 -4 M ) resulted in a n apparent inhibition o f the CRH-41 release into the push-pull system. However, as n o true synaptic contacts have ever been demonstrated between catecholaminergic and CRH-41 -producing nerve terminals in the M E , a n d as a recent cxperiment with the same infusion procedure showed that at least 40% of the dopamine injected into the M E was actually trapped by M E nerve terminals (28), the physiological significance of high-dose infusions into the M E is questionable. Finally, it should be remembered that the CRH-41 concentrations measured in the push-pull perfusate under o u r experimental conditions stayed below the sensitivity threshold o f the RIA in several perfusion samples, which markedly reduces the precision of estimates of inhibitory regulations a t this far end of CRH-41-secretion neurons.…”
Section: Discussionmentioning
confidence: 99%